Port assisted closure of laparoscopic wound: A safe and feasible technique - Leow, Voon Meng; Mohd Sikandar, Faizah; Sharif, Mohd Sharifudin; Letchumanan, Vasu Pillai; Khuan, Fuat Yang; Subramaniam, Manisekar K. (Malaysian Medical Association, 2015)
Objective: Various techniques and instruments have been developed to provide safe and secure closure of laparoscopic wounds. Herein we describe a simple method to close laparoscopic supraumbilical wounds with the aid of a laparoscopic port. Method: This was a retrospective review of prospective data, which were from 151 patients who underwent laparoscopic cholecystectomy for symptomatic gallstone disease from December 2009 to December 2010 in Sultanah Bahiyah Hospital. A senior consultant hepato-pancreato-biliary (HPB) surgeon and two HPB trainee surgeons performed the operations. Postoperatively, all patients were followed up at 4 weeks. Results: All patients successfully underwent closure of the supraumbilical wound with the assistance of a 5mm laparoscopic port. None of the patients had incisional hernia on follow up. Conclusion: Port assisted closure of supraumbilical laparoscopic wounds is a feasible and safe technique.